Computer prediction of biological activity of 2-methyl(phenyl)-6,9-epoksybenzo[g]quinoline-4,5,10-Trion and 5-methyl-(1,2,4-triazolo[4,3-a] quinoline) - Yu. V. Karpenko; , O. A. Brazhko; L. O. Omelyanchik (Zaporozhye State Medical University, 2015)
, One of the priority measures, which are evaluated in the creation of new effective medicines, is their high selective effect and lack of side effects. A considerable interest is the possibility of combining several structures of heterocycles in one molecule, such as quinoline and furan, which may cause an increase in biological activity of these combined compounds or an emergence of new properties. It is known that derivatives of 1,2,4-triazolo[4,3-a]quinoline have anticonvulsant effect and treat the syndrome of disorders with the nervous system. The aim of research. The main purpose of this work was an establishment of combinatorial library of bioregulators, which combines structures 5,8-dioksoquinoline and furan (1-8), quinoline and triazole (9-12), using computer program PASS (Prediction Activitity Spectra for Substances). Virtual screening of heterocycles derivatives was conducted to determine the direction of their bioactivity researches. Materials and methods. The virtual screening of compounds was performed by using the computer program PASS (Prediction Activity Spectra for Substances). For the specific activity the increase of Pa quantity and the decrease of the Pi quantity, helps to get the greater chance to detect this activity in the experiment. Predicting the probability of substance manifestation of specific types of biological activity determines which tests are the most appropriate for studying the biological activity of specific chemical substances and which substances of those that are available to the researcher likely will show the desired effect. With theoretical prediction the most likely basic structures of new compounds with desired biological effect, which best suits the task will be selected. Results. Analysis of computer prediction demonstrates the promising search of antineoplastic, antibiotic, analgesic and other types of activity in some of these compounds. An important instant of prediction of these substances is their lack of high toxicity terato-, kantsero-, embryo- and mutagenicity. The computer prediction of derivatives of triazole[4,3-a]quinolone had shown that the substitution of hydrogen on the carboxylic acid residue decreases the expected activity, but significantly expands its range and appears new types of biological activity. Injecting the propionic acid residue, you can observe an antieczematic activity, but injecting propylene - antiviral and antiinflammatory activities. Amidation of carboxylic acids leads to a decrease in the activity of "structure-leader" and the emergence of new activities, such as antineurotic, antinociceptive and muscle relaxant. Conclusion. Data of the computer prediction shows us the promising search of the following two directions of bioregulators that can exhibit antineoplastic, antiradical, analgesic, antiinflammatory, diuretic and other biological activities.